EFFECT OF ALCOHOL RATIO AND REACTION TEMERATURE ON THE BIODIESEL PRODUCTION FROM USED COOKING OIL - A. Al-Tabbakh, Aouf; A. Mohammed, Amer; A. M. Habib, Nassir (Journal of Engineering and Sustainable Development, 2016)
Biodiesel, or alkyl ester, is an alternative renewable, biodegradable and non-toxic diesel fuel produced by catalytic transesterification of oil. It can be successfully employed in diesel engines and liquid fuel burners. The present work deals with a system for transesterification of vegetable oil using a stirring reactor. Used cooking oil is employed for this purpose due to its availability and cost-effectiveness. The transesterification of oil was carried out using molar ratios (oil: methanol) of (1:9, 1:7, 1:5, 1:3) and reaction temperatures of (45, 55, 60, 70 oC). Sodium Hydroxide NaOH was used as a catalyst by an amount of 1% of oil weight and a stirring speed of 500 rpm was applied for 2 hours. The results showed that the production of biodiesel depends on the molar ratio of (oil: methanol) and on the reaction temperature. The optimal values that gave the highest productivity of biodiesel occurred at the molar ratio of (1:7) (oil: methanol) at a reaction temperature of (60 oC) in the presence of NaOH as a catalyst by an amount of 1% of the oil weight.